Gender and the public sector : professionals and managerial change - Barry, Jim, 1950-; Dent, Mike, 1944-; O'Neill, Maggie (Routledge advances in management and business studies, 2003)
Drawing on sociology and social policy, this intriguing volume considers various aspects of gender and professional identity. Contributors explore the inter-relationship between managerialism, professionalism and gender identity in Britain, and examine the processes and impacts of change on those working in public sector organizations in other countries as they come under varying managerial pressures. The subject is viewed from a variety of perspectives, including feminism and post-modernism. With an international range of contributors, this important book brings together an array of.